An Investigation on the Application of Earned Value Management (EVM) in Managing Cost Performance - Lum, Seon (2015)
Although majority understands the significant of triple constraints of time, cost and quality in succeeding a project; however, the cost and time overruns are still the most critical problems encountered in construction project. Gantt chart S — curve is a common traditional tool that is used in the construction industry to monitor project performance. A good project schedule certainly assist better project plan in detail, however project implementation is the key success of any project. Earned Value Management (ISVM) is one of the fundamental approaches acting as a sound management tools towards the improvement upon the standard comparison of budget and actual cost which lacks an adequate indicator of progress. To address this, this research was conducted quantitatively to identify the percentage usage of EVM in Kuala Lumpur and Selangor construction industry, to examine the extent of EVM contribution compared to Gantt chart S - curve and to identify’ the challenges faced by using I3VM. 100 questionnaires are distributed to focal groups from contractor firm, consultant firm and project management firms. Feedbacks from 33 respondents revealed that majority agreed that EVM contributes to project cost monitoring and it provides an overall cost effective cost management tools. Besides, the three major challenges encountered using EVM is due to the lack of FVM knowledge, expertise and experience in the industry, lack of motivation and top management support and tedious data collection required when implementing EVM.